Do Salivary Cullin7 Gene Expression and Protein Levels Provide Advantages over Plasma Levels in Diagnosing Breast Cancer? - Ceren Tilgen Yasasever; Derya Duranyıldız; Süleyman Bademler; Hilal Oğuz Soydinç (Current Issues in Molecular Biology, 2024)
In addition to the tumor suppressor role of Cullin 7 (Cul7), one of the proteins belonging to the Cullin (Cul) family, studies have also suggested that Cul7 may act as an oncogene under certain conditions. The role of the Cul7 molecule in breast cancer is still unclear, and understanding its function could have significant implications for identifying novel therapeutic targets or improving diagnostic strategies in breast cancer management. In this study, the levels of the Cul7 molecule in plasma and noninvasive material saliva were investigated, and its possibility as a marker for breast cancer was discussed. Protein levels of blood and saliva samples taken from breast cancer patients and a healthy control group were measured by the ELISA (Enzyme-Linked Immunosorbent Assay) method. Gene expression levels between the two groups were analyzed by the qPCR (quantitative Polymerase Chain Reaction) method. In our study, Cul7 mRNA and protein expression levels were examined in 60 breast cancer patients and 20 healthy female controls, and a statistically insignificant difference was found between the patient and control groups in both plasma and saliva samples (p > 0.05). No correlation was found between the clinical characteristics of the patients and plasma and saliva Cul7 gene expression and protein levels (p > 0.05). Considering the possibility of Cul7 being a biomarker at the protein and mRNA levels, plasma is thought to be a better study material for Cul7. Our findings suggest that in the context of a study on salivary material, the expression of Cul7 at the mRNA level may have better potential utility as a biomarker.